Online methods and tasks in research measuring the effects of processing instruction. Issue 2 (16th October 2020) - Benati, Alessandro
Abstract : Empirical research measuring the effects of processing instruction comes largely from offline tasks. This introductory article to the current special issue provides readers with the following: (1) a brief description of processing instruction; (2) a short review of previous offline research; (3) a review of more recent online studies measuring real-time sentence comprehension.